Uji Validitas Instrumen Keterampilan Proses Sains pada Materi Inovasi Bioteknologi pada Fase F - Ratih, Arista; Festiyed; Rivo Yulse Viza; Dian Purnama Ilahi; Lisa Utami (Universitas Cokroaminoto Palopo, 2024)
The low level of students' science process skills is one of the problems faced in the learning process. Aspects of science process skills formulate hypotheses, apply concepts, ask questions, plan experiments, conduct experiments, predict, interpret data, communicate, and conclude. The type of research used is development research. The development model used is the 4 D model (define, design, develop, and dessiminate). This research only tested the validity of the science process skills instrument. The instrument used was a science process skills validity questionnaire. The questionnaire consisted of material, construction, and readability. From the research that has been done, it is obtained that the science process skills instrument on the material of biotechnological innovation phase F 81% with a valid category. The instrument can be used to measure students' science process skills in biology subjects.